Analisis Peran Media Sosial dalam Peperangan Rohani (Spiritual Warfare): Strategi Pelayanan Digital dalam Menghadapi Disinformasi yang Mengikis Spiritualitas Kristen - Pujiwati (REDOMINATE Jurnal Teologi dan Pendidikan Kristiani, 2026)
This study examines the role of social media as a contemporary arena of spiritual warfare and its impact on Christian spirituality amid the growth of digital disinformation. Employing a mixed-method approach, the research combines quantitative surveys and qualitative interviews to identify patterns of religious disinformation and explain their influence on doctrinal understanding, worship practices, and the faith identity of church members. The findings indicate a negative relationship between exposure to disinformation and the depth and consistency of spiritual practices. They also reveal increasing theological confusion and the emergence of digital influencers as “alternative authorities” who shape religious interpretation outside established church guidance. In addition, low levels of media literacy and the church’s limited readiness for digital ministry further heighten believers’ vulnerability to misleading narratives. The study concludes that the digital sphere functions as a strategic field of spiritual warfare requiring an integrated theological, pastoral, and literacy-based response. Recommendations include developing theologically grounded media literacy programs, training digital ministry leaders, strengthening pastoral guidance online, and designing contextual, evidence-based church content for contemporary digital communities across diverse contemporary congregational settings and contexts.